Signaling pathways and defense mechanisms of ferroptosis - Liu, Jiao; Kang, Rui; Tang, Daolin (The FEBS journal, 2022)
As a type of lytic cell death driven by unrestricted lipid peroxidation and subsequent plasma membrane damage, ferroptosis occurs and develops because of sophisticated signals and regulatory mechanisms. The reactive oxygen species (ROS) used to initiate ferroptosis come from a variety of sources, including iron‐mediated Fenton reactions, mitochondrial ROS, and membrane‐associated ROS driven by the NOX protein family. Polyunsaturated fatty acid‐containing phospholipids are the main substrates of lipid peroxidation in ferroptosis, which is positively regulated by enzymes, such as ACSL4, LPCAT3, ALOXs, or POR. Selective activation of autophagic degradation pathways promotes ferroptosis by increasing iron accumulation to cause lipid peroxidation. In contrast, system xc–‐glutathione–GPX4 axis plays a central role in limiting lipid peroxidation, although other antioxidants (such as coenzyme Q10 and tetrahydrobiopterin) can also inhibit ferroptosis. A main nuclear mechanism of cell defense against ferroptosis is the activation of the NFE2L2‐dependent antioxidant response by transcriptionally upregulating the expression of antioxidants or cytoprotective genes. Additionally, the membrane damage caused by ferroptotic stimulus can be repaired by ESCRT‐III‐dependent membrane scission machinery. In this review, we summarize recent progress in understanding the signaling pathways and defense mechanisms of ferroptosis. Ferroptosis is a type of oxidative stress‐mediated cell death characterized by iron accumulation, lipid peroxidation, and plasma membrane damage. Excessive autophagy can promote ferroptosis, whereas ESCRT‐III‐mediated membrane repair can limit ferroptosis. In this review, we highlight the current understanding of the main signaling pathways and defense mechanisms of ferroptosis.